ENTREPRENEURIAL SKILLS DELIVERY IN BUSINESS EDUCATION AND GRADUATE STUDENTS’ BUSINESS SUCCESS IN RIVERS STATE (UNIZIK Journal of Marketing, 2025)
This study investigated the relationship between entrepreneurial skills delivery in business education and graduate students’ business success in Rivers State. Correlational research design was used. The participants for this study were 187 postgraduate students from the two (2) universities in Rivers State that are running Business Education Post Graduate program. Data were collected mainly through the use of questionnaire.  Data collected were analyzed using Pearson correlation. The findings of the study showed that: there is a significant relationship between creativity and business success of Graduate students in Rivers State; there is a significant relationship between communication skills and business success and lastly, significant relationship between financial management skills and business success of Graduate students in Rivers State. Based on the result, we concluded that delivery of entrepreneurial skills through creativity, communication skills, and financial management skills can greatly enhance the financial success, corporate social responsibility, and customer satisfaction of Graduate students. We suggested that business educators should adopt a blend of delivery mechanisms for the impartation of entrepreneurial delivery skills that are anticipated to promote the business success of students. The implication of this result is that there is possibility of using entrepreneurial skills delivery as a paramount facet of education, training, and impartation of relevant entrepreneurial skills into graduates for economic growth, enhancement and becoming successful in business
Keywords: Skills, Delivery, Business. Education and Success